Improved strategy for post-traumatic hydrocephalus following decompressive craniectomy: Experience of a single center - Wang, Kun; Guo, Hongbin; Zhu, Yinxin; Li, Jinjian; Niu, Huanjiang; Wang, Yirong; Cai, Xiujun (Frontiers in Surgery, 2023)
Background: Patients with head trauma may develop hydrocephalus after decompressive craniectomy. Many studies have referred one-stage cranioplasty (CP) and ventriculoperitoneal shunt (VPS) was applied to treat cranial defect with post-traumatic hydrocephalus (PTH), but the safety and efficiency of the procedure remain controversial. Methods: This is a retrospective cohort study including 70 patients of post-traumatic hydrocephalus (PTH) following decompressive craniectomy who underwent simultaneous (50) and separated (20) procedures of cranioplasty and VPS from march 2014 to march 2021 at the authors’ institution with at least 30 days of follow-up. Patient characteristics, clinical findings, and complications were collected and analyzed. Results: 50 patients of PTH underwent improved simultaneous procedures and 20 patients underwent staged surgeries. Among the cases, the overall complication rate was 22.86%. Complications suffered by patients who underwent one-stage procedure of CP and VPS didn’t differ significantly, compared with patients in the group of staged procedures (22% vs 25%, P=0.763). The significant difference was not observed in the two groups, regarding the complications of subdural/epidural fluid collection (4%/6% vs 0/2%, p=1.000/1.000), epidural hemorrhage (6% vs 4%, p=0.942), dysfunction of shunting system (0 vs 2%, p=0.286), postoperative seizure (8% vs 4%, p=1.000) and re-operation case (0 vs 2%, p=0.286). No case of subdural hemorrhage, incision/intracranial/abdominal infection, shunting system dysfunction or re-operation was observed in the group of simultaneous procedure. And complications including subdural/epidural fluid collection, subdural hemorrhage and incision/intracranial infection was not shown in the case series of staged procedure group. Conclusion: The improved simultaneous procedure of cranioplasty and VPS is effective and safe to treat cranial defect and post-traumatic hydrocephalus with low risk of complications.